KEARIFAN LOKAL MEMPERTAHANKAN “MAHAVANA” DALAM MENUNJANG PENGEMBANGAN AGROWISATA DI DESA JATILUWIH KECAMATAN PENEBEL KABUPATEN TABANAN - I Made Sarjana (Bumi Lestari Journal of Environment)
It is a fact that the people in Jatiluwih together with local government of TabananRegency have been conserving 1.299,687 hectars of their forest. It was motivated since theforest has a vital role on producing fresh air and water for local people. Data was collectedthrough e.g. indepth interview, observation and literature study. This article described thelesson learned from community of Jatiluwih on concerving their forest based on localgenious.Result of the research showed that Jatiluwih Community implemented three methodson preserving their forest. They are called wanasri such as: (1) mahavana, very restrictedarea, people are forbidden to cut down any tree, (2) tapawana, people allowed to changefunction to this area just for building tample, (3) srivana, allowed for changing of landusage, such as for farming activity, or building (house, school, poultry etc).Beside ecological role, the forest in Jatiluwih also has economic impact onincreasing their quality of life. It has also been becoming one of the tourist attraction oragrotourism object